Can tolerant values survive economic insecurity? The role of functional autonomy in mediating outsider threats in Turkey. (September 2022) - Babula, Michael; Neal, Mark; Ersoy-Babula, Alp Idil; Muschert, Glenn; Şentürk, Murat; Özsoy, Duygu; Reppas, Dimitrios; Pereira, Vijay
Abstract: This study examines whether host population values that encourage the toleration of outsiders can persist in conditions of economic insecurity. Inglehart et al. (2006) observed that war and economic insecurity produced xenophobia and in-group solidarity against foreigners in Iraq. At the psychological level of cultural values, Maslow (1943) suggested that individuals could gain functional autonomy or freedom from insecurity if they had previously satisfied security needs during their formative years. This thereby points to a possible delay in large scale transition from one value set to another when radical economic change occurs. Indeed, following Maslow, cultural values associated with tolerance of others could persist, at least for a while, even in times of abrupt economic depression or destruction. In this study, we set out to test this value lag due to functional autonomy, and chose Turkey as the test country. As a country that experienced economic growth and relative stability up until a sharp economic decline from 2016, Turkey offers an ideal environment to test the nature and influence of functional autonomy on host population responses to foreigners. In order to examine this, we analysed the results of 1073 questionnaires submitted to participants at Istanbul University and Atatürk University to examine levels of xenophobia. Mann Whitney tests confirmed detectably lower levels of xenophobia and less gender bias among needs-gratified respondents. The implications for political culture change are discussed.